2014
DOI: 10.1016/j.soard.2014.04.008
|View full text |Cite|
|
Sign up to set email alerts
|

Inferior vena cava filters and postoperative outcomes in patients undergoing bariatric surgery: a meta-analysis

Abstract: for the Cardiovascular Meta-analysis Research Group., Inferior vena cava filters and postoperative outcomes in patients undergoing bariatric surgery: a meta-analysis, Surgery for Obesity and Related Diseases, http://dx. doi. org/10.1016/j.soard.2014.04.008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Summary of the evidence. We identified 2 systematic reviews of RCTs and observational studies 137,138 that addressed this research question in bariatric surgery and trauma patients. We identified 14 studies [139][140][141][142][143][144][145][146][147][148][149][150][151][152] in these reviews that fulfilled our inclusion criteria and measured outcomes relevant to this context.…”
Section: Recommendationmentioning
confidence: 99%
“…Summary of the evidence. We identified 2 systematic reviews of RCTs and observational studies 137,138 that addressed this research question in bariatric surgery and trauma patients. We identified 14 studies [139][140][141][142][143][144][145][146][147][148][149][150][151][152] in these reviews that fulfilled our inclusion criteria and measured outcomes relevant to this context.…”
Section: Recommendationmentioning
confidence: 99%
“…Meta-analysis of six observational studies suggested higher risk of deep venous thrombosis (OR 2.81, 95% CI 1.33 to 5.97), similar risk of pulmonary embolism (RR 1.02, 95% CI 0.31 to 3.37) and a trend towards higher risk of mortality with inferior vena cava filters (RR 3.27, 95% CI 0.78 to 13.64), albeit with wide interval estimates ( Supplementary Table S9) [64]. Due to the importance of these outcomes and despite the low certainty of the evidence overall, this difference in effect estimates prompted the panel to provide a strong recommendation against the use of filters outside a research protocol.…”
Section: Strong Recommendationmentioning
confidence: 99%
“…Two papers were published recently in an attempt to address this issue. One was a meta-analysis that examined 6 papers culled from 701 abstracts [41]. The papers analyzed were a mix of prospective and retrospective cohorts and involved mostly open bariatric surgery.…”
Section: Research In Indicationsmentioning
confidence: 99%
“…Patients identified as highest risk included those with prior VTE, pulmonary hypertension, a personal or family history of coagulopathy, chronic immobility, preoperative lower extremity venous stasis, and those with the Bhighest^BMI. However, as with the meta-analysis by Kaw [41], a specific BMI value could not be provided due to the lack of uniformity of definitions used in the papers that were analyzed .…”
Section: Research In Indicationsmentioning
confidence: 99%